2018
DOI: 10.24840/2183-0606_006.003_0004
|View full text |Cite
|
Sign up to set email alerts
|

Mobile payments: A proposal for a context-oriented approach based on socio-technical theory

Abstract: A recent review of mobile payment research by Dahlberg et al. (2015) concludes that there is a need to synthesise this research area by studying contexts in which innovation is carried out and to integrate different aspects of research. This article aims to provide a proposal for how to achieve such integration and context orientation by building on previous studies and offering an additional review. Our systematic literature review of mobile payments research is focused on papers published during 2006–2016. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Having evolved from electronic payment (e‐payment), mobile payment has been widely adopted in the global market, which has been widely adopted in the market, and the use of this payment scheme has gained wide acceptance, particularly in China (Apanasevic et al, 2018; Liébana‐Cabanillas et al, 2018). According to Hotel Online (2015), Payment Week Reports reported that among the tourists from China who took a survey in http://hotels.com, 60% of them considered mobile payment as a decisive element in booking hotels.…”
Section: Introductionmentioning
confidence: 99%
“…Having evolved from electronic payment (e‐payment), mobile payment has been widely adopted in the global market, which has been widely adopted in the market, and the use of this payment scheme has gained wide acceptance, particularly in China (Apanasevic et al, 2018; Liébana‐Cabanillas et al, 2018). According to Hotel Online (2015), Payment Week Reports reported that among the tourists from China who took a survey in http://hotels.com, 60% of them considered mobile payment as a decisive element in booking hotels.…”
Section: Introductionmentioning
confidence: 99%
“…Specific attention needs to be put on the dynamics of competition with regard to new activities in the value chain, such as data analytics, and new players in the competitive ecosystem, such as IT service providers (Brito, 2018;Ili & Lichtenthaler, 2017). Acknowledging this strategic complexity and developing a systematic strategic approach is essential for achieving a competitive advantage (Apanesevic, Arvidsson, & Markendahl, 2018;Datta, 2018). While the growing competitive relevance of AI cannot be ignored, the core strategic impact will derive from the interplay of AI with human intelligence rather than from the pure implementation of AI.…”
Section: Discussionmentioning
confidence: 99%
“…Trust increases perceived value when shopping online. Researchers investigated the impact of perceived trust and discovered that it is one of the most influential elements in the service industry (Apanasevic et al 2012;Chang et al 2016;Hasan et al 2023b). As a result, perceived value is an important component which influences trust (Chang et al 2016;Yang and Peterson 2004;Gupta et al 2023).…”
Section: Perceived Value and Trustmentioning
confidence: 99%